2020
DOI: 10.1002/cctc.202001498
|View full text |Cite
|
Sign up to set email alerts
|

Fast Screening Method for Nitrogen Reduction Reaction (NRR) Electrocatalytic Activity with Rotating Ring‐Disc Electrode (RRDE) Analysis in Alkaline Environment

Abstract: The Haber‐Bosch process for NH3 production leads to a considerable greenhouse gas release due to the remarkable use of fossil fuels. Therefore, there is an increasing interest in developing alternative and environmental friendly approaches. Among the possible solutions, the electrocatalytic conversion of N2 has recently gained significant attention; on the other hand, not only scientific but also important technical aspects remain fundamental issues to be clarified. Particularly relevant is the need to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In a sustainable energy economy, alternatives for the large‐scale production of ammonia are urgently needed [11] . Here, electrochemical nitrogen reduction reaction (NRR), preferably in aqueous electrolytes because water as solvent is non‐toxic, comes into play [12–14] . The NRR, catalyzed by a solid‐state material, can be considered as an environmentally benign reaction route for ammonia formation if the required electricity is supplied from renewable solar or wind energy [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sustainable energy economy, alternatives for the large‐scale production of ammonia are urgently needed [11] . Here, electrochemical nitrogen reduction reaction (NRR), preferably in aqueous electrolytes because water as solvent is non‐toxic, comes into play [12–14] . The NRR, catalyzed by a solid‐state material, can be considered as an environmentally benign reaction route for ammonia formation if the required electricity is supplied from renewable solar or wind energy [15] .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Here, electrochemical nitrogen reduction reaction (NRR), preferably in aqueous electrolytes because water as solvent is non-toxic, comes into play. [12][13][14] The NRR, catalyzed by a solid-state material, can be considered as an environmentally benign reaction route for ammonia formation if the required electricity is supplied from renewable solar or wind energy. [15] Yet, this process is still in its infancy due to the low solubility of N 2 in water, the competing hydrogen evolution reaction (HER) under cathodic reaction conditions, and the slow reaction kinetics due to the transfer of six proton-electron pairs to form NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 0.01 M H 2 SO 4 solution was used to remove possible NH 3 in N 2 and Ar, and the de‐NO X tank was used to remove possible trace NO X impurities and water vapor from the gas. We cleaned all electrochemical components (sulfuric acid absorption solution, Nafion 211 membrane, catalyst and cathode chamber) and gas in the experimental device several times before each measurement [48,49] . The sweep rate of the linear sweep voltammetry (LSV) polarization curve in the experiment was 1.0 mV s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results indicated that the IC can be optimized to meet the low‐concentration quantitative requirements and the optimized ion chromatography with customized loop size was employed in our following experiments. Furthermore, the frequency‐selective NMR method as an advanced ammonia quantification method offers many advantages (high sensitivity, good reproducibility, straightforward discrimination against contaminant NH 3 , and convenience without the need for NH 3 transfer or advanced chemical manipulation) [11b] . Each 1 H NMR spectrum consists of an accumulation of 128 scans for a total experiment time of ≈10 min, which is comparable to the detection efficiency of ion chromatography.…”
Section: Figurementioning
confidence: 99%